Low-dose intravenous gammaglobulin in the treatment of severe autoimmune urticaria - Pereira, C (2012)
BACKGROUND: An autoimmune pathogenic mechanism is implicated in about one-third of patients with chronic urticaria (CU), involving circulating functional autoantibodies to either the high affinity IgE receptor (LgG1/IgG3 anti-FcARI) or to IgE, with histamine releasing activity. New therapeutic approaches had been developed for patients with severe or unresponsive to treatment symptoms, including the use of intravenous immunoglobulins (IVIG) as immunomodulators. AIM: To assess the efficacy of IVIG treatment in patients with evidence of autoimmune CU. METHODS: A group of 29 patients (F = 20, M = 9) with the diagnosis of autoimmune CU were selected from the outpatient department. All the patients showed daily symptoms of urticaria and/or angioedema, with unsatisfactory response to conventional therapy and a positive intradermal autologous serum test (AST). They were submitted to low dose of IVIG treatment each 4 weeks (0.15 g/kg), for a minimum of 6 months and a maximum of 51 months. They were evaluated for clinical scores, need of oral medication and AST results, before and after treatment. RESULTS: A clinical improvement was observed in 26 patients, with reduction of urticaria or angioedema complaints (p < 0.0001) and decreasing need for oral antihistamine medication (p = 0.002). 3 patients drop-out the treatment: one depending of severe adverse event and the other 2 with no response after the 5th treatment. 19:26 patients achieved complete remission of symptoms. A reduction of histamine-releasing activity was found in the majority of the patients, documented by the decrea, se of reactivity in AST at the end of the treatment (p = 0.002). 20 patients remained without symptoms during 12 months after. the active treatment, and the other 6 only reported non-severe complaints. CONCLUSION: IVIG is an effective therapeutic option in patients suffering from severe CU refractory to conventional treatment, in which autoimmune mechanism is involved. The efficacy persists for at least 12 months after treatment. However, the number of infusions needed to achieve clinical control, showed great range between patients.